The Training on Making Various Dried Flowers from Corn Husk Waste for Women Farmers Group Members (Kelompok Wanita Tani, KWT) - Arianti, Nyayu Neti; Rahmi Yuristia; Andi Irawan (Bengkulu Institute, 2025)
Dusun Baru II Village, Karang Tinggi District, Central Bengkulu Regency, Bengkulu Province is a corn-producing village. Members of the Women Farmers Group (KWT) in Dusun Baru II Village help their husbands farm corn. Corn husk waste from farming has not been utilized. The handling of this corn husk waste is only by burning it. Corn husk can be processed into animal feed, compost, or various dried flowers. Dried flowers with various shapes, sizes and colors can be made from corn husk so that they are attractive and have a selling value. The 25 women who are members of the KWT were the training activity targets make various dried flowers from corn husk. The aim of this activity is add knowledge and skills to process agricultural waste and turn them into goods of economic value that can increase family income. This training activity was carried out in September 2024 which included two activities, namely counseling on the utilization of corn husk and practicing making various dried flowers from corn husk with the principle of learning by doing. The women members of KWT participated in the activity with great enthusiasm because they had gained new skills to utilize the corn farming waste. Keywords: corn husk; dried flower; training